To find the sum of a specific geometric series, you can use a simple formula:
S_n = a × (1 - r^n) / (1 - r)
Let's break down what this means:
Let's look at this series: 2, 6, 18, 54, ...
In this case:
Now, we can use the formula:
S_4 = 2 × (1 - 3^4) / (1 - 3)
S_4 = 2 × (1 - 81) / (-2)
S_4 = 2 × 40
S_4 = 80
So, the sum of the first four terms is 80.
To find the sum of a specific geometric series, you can use a simple formula:
S_n = a × (1 - r^n) / (1 - r)
Let's break down what this means:
Let's look at this series: 2, 6, 18, 54, ...
In this case:
Now, we can use the formula:
S_4 = 2 × (1 - 3^4) / (1 - 3)
S_4 = 2 × (1 - 81) / (-2)
S_4 = 2 × 40
S_4 = 80
So, the sum of the first four terms is 80.